(untitled) (Journal of history, 2025)
The study of historical and geographical data on individual cities and entire regions allows us to determine the features of their development. Usually, researchers obtain this data from sources of past eras. One of them is the encyclopedia of the Mamluk official Al-Qalkashandi, «The Dawn for the Blind in the Art of Writing». The current article aims to reveal the meaning of «The Dawn…» for historical geography in the context of the methods of describing cities and regions used by Al-Qalkashandi in the encyclopedia. To achieve this goal, the works of Kazakh and foreign researchers were analysed, and excerpts from «The Dawn…» itself were used. Data monitoring, comparison, historical-critical approach, and specification were chosen as the research methods. The application of this entire set of methods allowed us to create our methodology, which determined the complexity of this study—as a result of the analysis revealed a connection between the geographical location of regions and cities and their system of administration, power transfer and lifestyle of their inhabitants. The results also showed that Al-Qalqashandi actively used historical geography methods, although it did not even exist as a science during his lifetime. This indicates the importance of his work for historical geography, establishing Al-Qalqashandi as one of the first researchers who understood the connection between geographical indicators and the dynamics of the development of the territories that he described in «The Dawn…». The prospect of further research is to compare the description of cities and regions that Al-Qalqashandi made with information from his contemporaries to analyse the reliability of the facts presented in «The Dawn…».